2008
DOI: 10.1603/0046-225x(2008)37[850:uafmtm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Using Automated Flight Mills to Manipulate Fat Reserves in Douglas-fir Beetles (Coleoptera: Curculionidae)

Abstract: Because current techniques for quantifying fat, the main fuel used for flight in insects, are destructive, researchers are limited to only one direct measure of fat per specimen. This limitation is problematic for studies aimed at assessing whether fat loss through flight influences subsequent behavioral activity. To overcome this problem, we used body volume, body mass, emergence day, and brood density as parameters in a multiple regression model to predict initial fat levels in female Douglas-fir beetles, De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Since these factors do not show spatial homogeneity at landscape scale, the distribution of infestation patches reflects the most preferred localities. Nevertheless, dispersal distances are generally determined by a combination of the specific flight capacity and host selection behavior of the individuals, which vary within populations (Wallin and Raffa, 2004;Williams and Robertson, 2008;Hawkes, 2009), as well as of the spatial availability of suitable habitats. When attacking living trees a pheromone mediated mass attack is necessary to overcome the tree's defense (Byers, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Since these factors do not show spatial homogeneity at landscape scale, the distribution of infestation patches reflects the most preferred localities. Nevertheless, dispersal distances are generally determined by a combination of the specific flight capacity and host selection behavior of the individuals, which vary within populations (Wallin and Raffa, 2004;Williams and Robertson, 2008;Hawkes, 2009), as well as of the spatial availability of suitable habitats. When attacking living trees a pheromone mediated mass attack is necessary to overcome the tree's defense (Byers, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In European corn borer, adult weight of both sexes, and therefore energy reserves, was severely negatively affected by Nosema infection. The greater prevalence of negative effects of Nosema infection on male than female flight performance observed in our study may reflect lesser energy reserves in the smaller males (Williams and Robertson 2008; Elliott and Evenden 2009). Even in the presence of adequate energy reserves, the parasite may interfere with the host’s physiological ability to utilize them (Seyoum et al.…”
Section: Discussionmentioning
confidence: 53%
“…Although our estimates are imprecise due to the lack of knowledge about the effective density and (possibly) its variability over the studied area, dispersal of several hundred meters is highly possible in this species. Zauli et al (2014) found that males of E. ferrugineus moved from the site of first capture covering a median distance of 214 m and approximately 50 % of individuals disperse not further than 250 m. Observed movement distances of other saproxylic beetles could comprise more than 700 m in a species which is believed to be poor flier (Dubois et al 2010;Oleksa et al 2013a) and even more than 10 km for species with high dispersal capacities (Jonsson 2003;Williams and Robertson 2008;Drag et al 2011). In this respect, E. ferrugineus can be regarded as a species with lower dispersal abilities, for which habitat continuity plays an important role.…”
Section: Discussionmentioning
confidence: 99%